M MEMAHAMI HAKEKAT KEPRIBADIAN MUSLIM DAN PEMBENTUKANNYA MELALUI PENDIDIKAN DALAM ISLAM - AYU DEVI SETIOWATI (Raudhah - Proud To Be Professional, 2022)
In essence personality does not occur immediately but is formed through a very long life process, while the target to be addressed in personality formation is personality having noble character. The level of moral nobility is closely related to the level of faith. Therefore the Prophet Muhammad S.A.W said that "the most perfect believer in faith is the believer with the best morals". The Al-Qur'an and Sunnah are the heritage of the Prophet Muhammad which must be referred to by Muslims in all aspects of life, one of which is the formation and development of the Muslim personality. The Muslim person that the Al-Qur'an and Sunnah want to achieve is a pious person, a person whose attitudes, speech and actions are colored by the values ​​that come from Allah SWT. In addition, there are elements of Muslim personality which will be discussed here.